An assessment of the CMM Implementation at CIS - Sy, Susan A. (Technology Management Center, 2009)
The concern for quality has become an international movement, and a very popular way to improve quality is to improve the software process. Software Process Improvement (SPI) is thus defined as : the application of technology and disciplines to improve software development and maintenance processes. This project aimed to conduct an assessment on the effectiveness of the Capability Maturity Model (CMM) implementation at Company XYZ. It provided a reality check with respect to the effects of the implementation on the business performance and organizational behavior of the Company. Also, the compliance and degree of assimilation, acceptance and process fidelity have been examined. Specifically, this project aimed to identify the major issues evolved in implementing the CMM Level 3 for the SPI movement, and then recommendations are to be proposed, and lessons learned are also cited. The scope of this study included only the employees of the Company's Solution Center, the department that is responsible for delivering software projects; these employees are all technically skilled personnel who are knowledgeable in the software developmental process. For the methods of research, the proponent used Internet and library research in order to obtain the relevant information needed for the project. Interviews and surveys were conducted among the proponent's colleagues for her to avail of the first hand information as guide in achieving the project objectives. Started as a spin-off company from the Electronic Data Processing (EDP) department of Company ABC last 1974, Company XYZ has eventually established its place in the local Information Technology (IT) market, and has been started to venture into the International IT market. The Company, under the directive of its new leader, had set its eye at the international market, and it is counting on the accreditation of CMM Level 3 as another credential for it to acquire the approval of international prospective clients. And thus the Company had launched a Software Process Improvement (SPI) movement, using the CMM as its process model framework. CMM is a common-sense application of the process management and quality improvement concepts to software development and maintenance. It is an IT community-developed guide for evolving towards a culture of software engineering excellence; a model for organizational improvement; and the underlying structure for reliable and consistent software process assessments and software capability evaluations. Moreover, CMM has emerged as the quality standard in the software services arena, it is often used by the CIOs as a mechanism to rank and rate service providers. This process model that was created and maintained by the Software Engineering Institute is a project in response to the United States Air Force's frustration with its software buying process in the 80's. Company XYZ attained SW-CMM (Capability Maturity Model for Software) Level 3 rating from an authorized SEI lead appraiser, making it the first Filipino-owned IT Company to earn this distinctive recognition. This achievement re-emphasizes the Company's continuous commitment to product quality and customer service. In preparation for the CMM accreditation, Company XYZ adopted a set of guidelines by following the IDEAL framework in defining the steps necessary to establish a continuous improvement program based on the CMM : 1. Set up a process improvement team, 2. Model the existing process. 3. Conduct qualitative process. 4. Define and document an action plan. 5. Set up a measurement program. 6. Perform a pilot project. 7. Change the process and the organization. In 2003, the organization familiarized itself with a software process standard named SW-CMM. There was an assumption that this specialized process model would provide a clearer direction for the improvement of the software process. The SW-CMM was chosen due to some considerations : 1. SW-CMM provides a road map for process improvement. 2. SW-CMM is an accepted industry standard. 3. Management was most attracted by the general project and quality management practices. 4. SW-CMM is based on actual experience and reflects the best practices. 5. Numerous success stories of how the SW-CMM can improve productivity and time to market, and decrease product defects. The decision was made to start a SPI effort to achieve SW-CMM Level 3 compliance. The results of this effort are presented in this paper. Here are presented the main issues and problems encountered in the improvement efforts : 1. Organizational Scope. Because the initiative is not carried out organization-wide, the project managers don't feel assured, that the decisions made, and procedures created, especially when they somehow involve other organizational units (for example, relations with the Sales and Marketing Department), will be supported. This way they are less motivated to change.